2019
DOI: 10.1371/journal.pone.0210730
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary approach is associated with improved survival of hepatocellular carcinoma patients

Abstract: BackgroundGiven the complexity of managing hepatocellular carcinoma (HCC), a multidisciplinary approach (MDT) is recommended to optimize management of HCC patients. However, evidence suggesting that MDT improves patient outcome is limited.MethodsWe performed a retrospective cohort study of all patients newly-diagnosed with HCC between 2005 and 2013 (n = 6,619). The overall survival (OS) rates between the patients who were and were not managed via MDT were compared in the entire cohort (n = 6,619), and in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 30 publications
(42 reference statements)
0
63
0
2
Order By: Relevance
“…Intuitively having MTB and therefore a group of experts discuss every case is the obvious choice, but the literature is not as clear yet concerning the evidence for an improved clinical outcome. While many single tumor entity group studies show an improvement in OS [1][2][3][4][5][6][7][8] some found no relevant improvement of the clinical outcome [9,10]. Studies evaluating OS in MTB across different tumor entity groups by literature reviews [13] or comparison of centers with and without MTB [14] show weak to no evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intuitively having MTB and therefore a group of experts discuss every case is the obvious choice, but the literature is not as clear yet concerning the evidence for an improved clinical outcome. While many single tumor entity group studies show an improvement in OS [1][2][3][4][5][6][7][8] some found no relevant improvement of the clinical outcome [9,10]. Studies evaluating OS in MTB across different tumor entity groups by literature reviews [13] or comparison of centers with and without MTB [14] show weak to no evidence.…”
Section: Discussionmentioning
confidence: 99%
“…While the number of tumor boards continued to grow over this period, it is important to evaluate the benefit of this effort for the patient. Previous studies were able to show improvement of survival for some specific tumor entity groups like lung cancer [1][2][3], head and neck cancer [4,5], hepatocellular cancer [6,7] and breast cancer [8] while some other studies did not show an significant improvement of survival for entities like pancreatic cancer [9] colorectal cancer [10], multiple myelomas [11] or metastatic germ cell tumors [12]. Analyses which tried to draw the big picture by taking multiple entities into consideration via metanalysis [13] or general comparison of cancer centers with and without multidisciplinary tumor board meetings [14] showed little to no evidence of an improved clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…This vulnerable patient group is likely to have more liver‐related comorbidities that require close surveillance. Thus, in patients with HCV‐related HCC, particularly with the presence of cirrhosis, monitoring of liver function and the selection of DAA regimens should be considered, preferably via multidisciplinary approach (MDT)—which is becoming a common practice in many tertiary medical centres—to achieve optimal treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…To select the factors for multivariate analysis, the stepwise procedure was used as previously described . Although the BCLB staging system includes liver function and tumor size, both the BCLC staging system and ALBI score were applied for the stepwise procedure as previously described . Factors associated with overall survival were evaluated using multivariate and decision‐tree analyses as previously described .…”
Section: Methodsmentioning
confidence: 99%